2012
DOI: 10.1002/qre.1413
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Parameter Estimation on Upper‐sided Bernoulli Cumulative Sum Charts

Abstract: The Bernoulli cumulative sum (CUSUM) chart has been shown to be effective for monitoring the rate of nonconforming items in high-quality processes where the in-control proportion of nonconforming items (p 0 ) is low. The implementation of the Bernoulli CUSUM chart is often based on the assumption that the in-control value p 0 is known; therefore, when p 0 is unknown, accurate estimation is necessary. We recommend using a Bayes estimator to estimate the value of p 0 to incorporate practitioner knowledge and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 16 publications
2
43
0
Order By: Relevance
“…These approaches would be useful in cases where one has not completed a thorough phase I study resulting in the estimation of the parameters of the now stable process as well as the types and magnitudes of shifts that can occur. See, for example, Bischak and Trietsch, Castagliola et al, Lee et al, Zhang et al, Aly et al, Saleh et al, Epprecht et al, Loureiro et al, and Faraz et al More information on this topic can be found in a thorough literature review in Jensen et al and more recently in Psarakis et al Gandy and Kvaløy proposed a bootstrap method to adjust control limits such that Pr (ICARL > C ) = (1 − p 1 ). Saleh et al and Faraz et al extended this approach to the EWMA and Shewhart control charts respectively.…”
Section: Design Of the Truex¯ And S2 Control Charts With The Percentmentioning
confidence: 99%
“…These approaches would be useful in cases where one has not completed a thorough phase I study resulting in the estimation of the parameters of the now stable process as well as the types and magnitudes of shifts that can occur. See, for example, Bischak and Trietsch, Castagliola et al, Lee et al, Zhang et al, Aly et al, Saleh et al, Epprecht et al, Loureiro et al, and Faraz et al More information on this topic can be found in a thorough literature review in Jensen et al and more recently in Psarakis et al Gandy and Kvaløy proposed a bootstrap method to adjust control limits such that Pr (ICARL > C ) = (1 − p 1 ). Saleh et al and Faraz et al extended this approach to the EWMA and Shewhart control charts respectively.…”
Section: Design Of the Truex¯ And S2 Control Charts With The Percentmentioning
confidence: 99%
“…When considering the number of conformities between two adjacent nonconformities in a high‐quality process, the matter of great importance is not the number of consecutive nonconformities when there is an out‐of‐control signal but the total number of both the conforming and nonconforming observations to signal . Moreover, as different phase I sample sizes the practitioners choose do have an influence on the estimation of the control limits, the practitioner‐to‐practitioner variability in the in‐control average number of observations to signal (ANOS) should also be considered, which is the standard deviation of the average number of observations to signal (SDANOS) . Among them, the in‐control ANOS represents the average number of observations to signal when there is a false alarm in the in‐control process.…”
Section: Introductionmentioning
confidence: 99%
“…Of course, small SDARL 0 values mean that the ARL 0 values will be close to the desired value B . Zhang et al ., Lee et al . and Faraz et al .…”
Section: Introductionmentioning
confidence: 99%